Linfoma de Hodgkin: características anátomo-clínicas e análise de novo biomarcador (IMP3) - Moraes, Marcelo Padovani de Toledo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Hodgkin lymphoma (HL) is a hematopoietic neoplasm that characteristically affects young adults and, if untreated, presents a fatal clinical course. Early and accurate diagnosis of this lymphoma associated with modern therapeutic management, on the other hand, has promoted a dramatic decrease in mortality rates. Despite this, around 15-20% of patients show unsatisfactory progression, with resistance to primary therapy or early relapse following treatment. The literature comprises numerous studies attempting to determine prognostic profiles that are capable of selecting candidate patients for specific therapies. Insulin-like growth factor mRNA binding protein 3 (IMP3) has been described as a biomarker that indicates worse prognosis in several malignancies, particularly carcinomas; however, studies of IMP3 in hematopoietic malignancies are rare. To assess their potential prognostic role in HL, IMP3 expression was studied in 61 cases and included stratification of immunostaining intensities (0, +, ++ and +++) and their relation to status of life, clinical data and morphological and immunohistochemical features. Intense IMP3 expression (+++) was observed in 61% (34/56) cases and showed a strong indication of association with better disease-free survival. Our findings show that IMP3 is a potential biomarker of better prognosis in HL

O Linfoma de Hodgkin (LH) é uma neoplasia hematopoiética que acomete caracteristicamente adultos jovens e apresenta, quando não tratado, curso clínico fatal. O diagnóstico precoce e preciso desse linfoma, associado à terapia moderna, por outro lado, tem proporcionado diminuição dramática das taxas de letalidade. Ainda assim, cerca de 15-20% dos pacientes evoluem de maneira insatisfatória com resistência a terapia primária ou recaída precoce pós-tratamento. Nesse sentido, há estudos variados na tentativa de buscar perfis prognósticos capazes de selecionar pacientes candidatos a terapias particulares. O IMP3 (insulin-like growth factor mRNA binding protein 3) tem sido descrito como biomarcador relacionado a pior prognóstico em diversas neoplasias, especialmente carcinomas, mas ainda pouco estudado em neoplasias hematopoiéticas. Para avaliar seu potencial papel prognóstico no LH, foi estudada a expressão do IMP3 em 61 casos, incluindo estratificação da imunocoloração em intensidades (0, 1+, 2+ e 3+) e relação com sobrevida, dados clínicos, aspectos morfológicos e imuno-histoquímicos. A expressão forte (intensidade 3+) para IMP3 foi observada em 61% (34/56) dos LH e apresentou forte indicio de associação com melhor sobrevida livre de doença. Nossos achados mostram o IMP3 como potencial biomarcador de melhor prognóstico em LH
Keywords: Hodgkin, Doença de; Linfoma; Prognostico; Revisão; Marcadores bioquímicos; Hodgkin's disease; Biochemical markers